Prescribing lithium for the management of persons suffering from bipolar disorders: expert consensus based on a Delphi study - Gaia Sampogna; Isabella Berardelli; Umberto Albert; Giulio Perugi; Maurizio Pompili; Alfonso Tortorella; Mirko Manchia; Gabriele Sani; Andrea Fiorillo (International Journal of Bipolar Disorders)
Abstract Background According to international guidelines, lithium treatment represents the gold standard for the appropriate management of persons with bipolar disorder. However, prescription rates in ordinary practice are not in line with clinical guidelines’ suggestions. Clinicians prefer to use drugs other than lithium, considering its low therapeutic window, the need for regular lab tests and its side effects profile. Based on these premises, a Delphi-method study focused on highly-debated aspects of lithium treatment in bipolar disorder has been promoted with the aim to reach a consensus among an expert panel of Italian psychiatrists. Methods The Delphi method is a structured technique aimed to obtain a consensus from repeated rounds of questionnaires where opinion/agreement among experts are important. A Steering Committee of experts has developed a 24-items questionnaire exploring: (1) the use of lithium as first choice for treating different phases of bipolar disorder; (2) the side effect and tolerability profile of lithium treatment as hampering factors for its use in clinical practice; (3) the lithium prescribing in special target population, such as adolescents, elderly patients, and pregnant women. Results The questionnaire was delivered to a panel of 100 Italian psychiatrists, experts in the field of managing people with bipolar disorders. An almost complete positive consensus was reached for statements dealing with the use of lithium treatment as first choice in the management of patients with bipolar disorder, and as the first choice for preventing manic/hypomanic and depressive episodes. Conclusions Current clinical guidelines and scientific evidence support the use of lithium as first choice treatment in patients with bipolar disorder. However, over the last decades a downward tendency in lithium’s prescription has been registered worldwide. The present Delphi study confirmed the “good clinical reasons” for supporting lithium prescription in clinical practice. Our findings should be used to develop clinical practice guidelines and reduce the discrepancy between international guidelines and ordinary care.